Pasteurellosis Transmission Risks between Domestic and Wild Sheep - Miller, Michael W.; Knowles, Donald P.; Bulgin, Marie S. (Council for Agricultural Science and Technology (CAST), 2008)
Native North American wild sheep species are very susceptible to pneumonia and particularly to pasteurellosis. Although the current understanding about pasteurellosis in wild and domestic sheep is incomplete, respiratory disease clearly is a serious problem in both. This Commentary discusses pneumonic pasteurellosis in domestic sheep, pasteurellosis in wild sheep, and the risks to wild sheep associated with domestic sheep interactions. The authors also address research needs and strategies for minimizing the risk of interspecies disease transmission.
Keywords: Pasteurellosis; Pneumonia; Wild Sheep; Domestic Sheep; Interspecies Disease